2018
DOI: 10.1371/journal.pone.0190782
|View full text |Cite
|
Sign up to set email alerts
|

RPA and XPA interaction with DNA structures mimicking intermediates of the late stages in nucleotide excision repair

Abstract: Replication protein A (RPA) and the xeroderma pigmentosum group A (XPA) protein are indispensable for both pathways of nucleotide excision repair (NER). Here we analyze the interaction of RPA and XPA with DNA containing a flap and different size gaps that imitate intermediates of the late NER stages. Using gel mobility shift assays, we found that RPA affinity for DNA decreased when DNA contained both extended gap and similar sized flap in comparison with gapped-DNA structure. Moreover, crosslinking experiments… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 58 publications
1
20
0
Order By: Relevance
“…RPA can protect single-stranded DNA from nuclear degradation and hairpin formation after DNA damage [43]. At the same time, RPA1 and RPA2 can bind to XPA to form the RPA-XPA complex, which is involved in the recognition of DNA damage [44]. In this study, we found that the mRNA and protein expression of RPA1, RPA2 decreased in FA-treated cells compared with control cells, indicating that RPA1, RPA2 did not participate in the repair of DNA damage caused by FA.…”
Section: Discussionmentioning
confidence: 99%
“…RPA can protect single-stranded DNA from nuclear degradation and hairpin formation after DNA damage [43]. At the same time, RPA1 and RPA2 can bind to XPA to form the RPA-XPA complex, which is involved in the recognition of DNA damage [44]. In this study, we found that the mRNA and protein expression of RPA1, RPA2 decreased in FA-treated cells compared with control cells, indicating that RPA1, RPA2 did not participate in the repair of DNA damage caused by FA.…”
Section: Discussionmentioning
confidence: 99%
“…The structure containing a damaged flap and a 26 nt gap imitates the DNA intermediate arising in the NER process after damaged strand cleavage by XPF‐ERCC1; DNA with the same flap and a 10 nt gap can be attributed to the intermediate of the subsequent partial gap filling . Crosslinking with 5‐I‐dUMP containing flap‐gap26 DNA revealed that RPA interacts with the ssDNA track in the gap and does not utilize the flap . Based on this study, it may be supposed that, after XPF‐ERCC1 incision, RPA remains bound with the undamaged strand in the gap created and can be translocated on the flap when gap is shortened during the resynthesis step (Fig.…”
Section: Rpa Positioning On the Ner Dna Intermediatesmentioning
confidence: 81%
“…From the NER factors, only RPA participates during all stages of the repair process. Using 60‐mer DNA duplexes containing a 31 nt flap with the fluorescein residue mimicking the bulky lesion and a 26 or 10 nt gap, RPA and XPA interactions with intermediates of the NER late stages were analyzed . The structure containing a damaged flap and a 26 nt gap imitates the DNA intermediate arising in the NER process after damaged strand cleavage by XPF‐ERCC1; DNA with the same flap and a 10 nt gap can be attributed to the intermediate of the subsequent partial gap filling .…”
Section: Rpa Positioning On the Ner Dna Intermediatesmentioning
confidence: 99%
“…The NER operates through two subpathways: a global genome repair (GG-NER) and transcription coupled repair (TC-NER). The GG-NER subpathway acts on lesions present in the whole genome, with XPC and XPE as the main proteins that recognize the DNA damage, while the TC-NER recognizes lesions during transcription elongation, when the RNA polymerase II is stalled by DNA damage found in the template strand [101,102].…”
Section: Removing Single-strand Breaks and Base Damage By Base Excision Repair And Bulky Lesions By Nucleotide Excision Repairmentioning
confidence: 99%